2017
DOI: 10.3892/etm.2017.4876
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic biomarkers for detection of acute exacerbation of chronic obstructive pulmonary disease with or without pulmonary embolism

Abstract: Abstract. Eosinophilia has been implicated in the pathophysiology of acute exacerbation of chronic obstructive pulmonary disease (AECOPD). However, the role of eosinophil activation in the development of AECOPD remains unclear. In the present study, the reliability of plasma levels of eosinophil activation markers, including eosinophil cationic protein (ECP), major basic protein (MBP), eosinophil-derived neurotoxin (EDN) and eosinophil peroxidase (EPX), were measured and used as diagnostic biomarkers of AECOPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
(49 reference statements)
1
10
0
Order By: Relevance
“…Yang et al . [ 59 ] suggested that the activation of eosinophils increases the likelihood of thrombosis. However, it is unclear whether eosinophil activation markers can predict PE in patients with exacerbation of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al . [ 59 ] suggested that the activation of eosinophils increases the likelihood of thrombosis. However, it is unclear whether eosinophil activation markers can predict PE in patients with exacerbation of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…RNase3 mRNA expression is also enhanced in induced sputum cells of stable COPD patients (n=12, mean age 70 years) compared to asthma patients (n=13, mean age 53 years) and non-smoker subjects (n=13, mean age 42 years), and there is a negative correlation between RNase3 mRNA expression and macrophages counts [370]. Furthermore, serum RNase3 levels are increased in COPD patients during exacerbation irrespective of the presence (n=30, mean age 72 years) or absence (n=47, mean age 74 years) of pulmonary embolism compared to healthy controls (n=35, mean age 71 years, not reported if smokers with normal lung function) [358].…”
Section: Rnasementioning
confidence: 89%
“…There are very few data in the literature on the role of Rnase2 in COPD. One study shows increased serum EDN levels in COPD patients during exacerbation irrespective of the presence (n=30, mean age 72 years) or absence (n=47, mean age 74 years] of pulmonary embolism when compared to healthy subjects (n=35, mean age 71 years, not reported if smokers with normal lung function) suggesting that recruitment and eosinophilic degranulation may have a key role in the pathogenesis of COPD exacerbations [358].…”
Section: Rnasementioning
confidence: 99%
“…Interestingly, PPAR-gamma, which was up-regulated by cannabis oil extract, can also counteract inflammation mediated by leukotriene B4 in COPD (Yin et al 2014 ). While eosinophil peroxidase does not appear to have been investigated as target for the treatment of COPD, it has been identified as a biomarker of the disease (Nair et al 2013 ; Yang et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%